Silicon-based negative pole piece and lithium ion battery comprising same
By designing two layers of active material in a silicon-based negative electrode sheet, combining high-quality silicon-based materials and porous crosslinked polymers, the problem of expansion and contraction of silicon-based negative electrode materials in lithium-ion batteries is solved, and higher cycling performance and energy density are achieved.
Patent Information
- Application Number
- CN202411831971.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-12
AI Technical Summary
The silicon-based negative electrode material will cause volume expansion and contraction during charging and discharging in lithium-ion batteries, resulting in increased mechanical stress, which will lead to breakage and powderization of silicon particles, seriously hindering the transmission of lithium ions and reducing the cycling performance of the battery.
A silicon-based negative electrode sheet is designed, adopting a two-layer active material layer structure. The first active material layer contains a high-quality silicon-based material and graphite, and combines a porous crosslinked polymer to buffer expansion; the second active material layer contains a low-quality silicon-based material and graphite, and uses a flexible binder to reduce expansion and contraction.
Through the design of two layers of active material, the silicon-based negative electrode sheet can effectively buffer expansion during charging and discharging, reduce mechanical stress, prevent the electrode sheet from peeling and cracking, and improve the cycling performance and energy density of the battery.
Smart Images

Figure CN119601587A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a silicon-based negative electrode plate and a lithium ion battery comprising the same. Background Art
[0002] In recent years, many mainstream car companies have gradually launched models equipped with silicon-doped negative electrode batteries, and the application of silicon-based negative electrodes has gradually expanded to the field of power batteries. As new battery technologies have been gradually put into use in recent years, the market space for silicon-based negative electrodes is also accelerating.
[0003] Silicon-based negative electrodes have a very high theoretical specific capacity (up to 4200mAh / g) and a low electrochemical lithium insertion potential, and excellent fast charging performance, which meets the development needs of the new energy vehicle field and is regarded as the next generation of ideal negative electrode materials. The mass energy density of lithium batteries using silicon-based negative electrode materials can be increased by more than 8%, while the cost per kilowatt-hour of the battery can be reduced by at least 3%. However, the silicon negative electrode will produce volume expansion and contraction during the process of lithium insertion and deintercalation, which can be as high as more than 300%, thereby generating great mechanical stress. After multiple cycles, the silicon particles will break and pulverize, which will seriously hinder the transmission of lithium ions inside the negative electrode, resulting in low initial efficiency and poor cycle performance.
[0004] Based on the demand for high energy density and fast charging performance of lithium batteries, the negative electrode materials of lithium batteries are accelerating to penetrate into silicon-based negative electrodes, and high-silicon systems will be the main direction of development. However, the use of high silicon will further increase the expansion and contraction of the negative electrode, leading to the peeling and pulverization of the negative electrode materials, and the deterioration of the cycle performance. Therefore, it is necessary to optimize the design of silicon-containing pole pieces to inhibit or buffer the expansion and contraction of the negative electrode high-silicon system, prevent the pulverization and peeling of the negative electrode particles, and thus improve the cycle performance. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention provides a silicon-based negative electrode plate, which, through a two-layer active material layer design, not only has a high energy density, but also can buffer the expansion of the silicon negative electrode during charging and discharging, and prevent the plate from peeling and cracking.
[0006] One of the objectives of the present invention is to provide a silicon-based negative electrode plate.
[0007] A second object of the present invention is to provide a lithium-ion battery comprising the silicon-based negative electrode plate.
[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0009] In a first aspect, the present invention provides a silicon-based negative electrode plate, comprising:
[0010] Anode current collector;
[0011] a second active material layer disposed on at least one surface of the negative electrode current collector;
[0012] a first active material layer disposed on a surface of the second active material layer;
[0013] The first active material layer includes the following components in mass percentage: 30-50% silicon-based material, 42-66% graphite material, 2-3% high-viscosity binder, 0.5-2% flexible binder, 0.1-2% conductive agent and 0.5-2% porous cross-linked polymer, the organic porous cross-linked polymer is obtained by polymerization of monomer 1 and monomer 2, monomer 1 is selected from one of hexabromotriptycene, hexaaminotriptycene, hexaphenyltriphenylene, trihydroxytriptycene and triaminotriptycene; monomer 2 is selected from one of 2,3-dimethylindole, 5-methyl-2,3-indoledione, indoline and indole-2,3-dione;
[0014] The second active material layer includes the following components in mass percentage: 5-10% silicon-based material, 85-93% graphite material, 1-2% flexible binder, 0-2% high viscosity binder and 0.1-2% conductive agent;
[0015] The high viscosity binder is one or more selected from polyacrylic acid, polyacrylonitrile, polytetrafluoroethylene, polyvinyl alcohol, and polybutyl acrylate;
[0016] The flexible binder is one or more selected from sodium carboxymethyl cellulose and styrene-butadiene rubber.
[0017] like Figure 1 As shown, the silicon-based negative electrode plate of the present invention comprises a negative electrode current collector 1, on which a second active material layer 2 and a first active material layer 3 are sequentially arranged.
[0018] The negative electrode current collector may be copper foil.
[0019] First active material layer:
[0020] The first active material layer includes the following components in mass percentage: 30-50% silicon-based material, 42-66% graphite material, 2-3% high viscosity binder, 0.5-2% flexible binder, 0.1-2% conductive agent and 0.5-2% porous cross-linked polymer.
[0021] The first active material layer is a mixed layer of a silicon-based material and graphite with a high mass ratio, which contains an organic porous cross-linked polymer and a high-viscosity binder combination.
[0022] The silicon-based material is one or more selected from nano-silicon oxygen, nano-silicon carbon, silicon nanowires, and amorphous silicon alloys;
[0023] The graphite material is one or more selected from artificial graphite, natural graphite and mesophase carbon microspheres.
[0024] The high viscosity binder is one or more selected from polyacrylic acid, polyacrylonitrile, polytetrafluoroethylene, polyvinyl alcohol, and polybutyl acrylate;
[0025] The flexible binder is one or more selected from sodium carboxymethyl cellulose and styrene-butadiene rubber.
[0026] The conductive agent is one or more selected from conductive carbon black, carbon nanotubes, graphene, conductive graphite, and carbon fiber.
[0027] The organic porous cross-linked polymer is obtained by polymerizing monomer 1 and monomer 2 in a chloroform solvent, wherein monomer 1 includes one of hexabromotriptycene, hexaaminotriptycene, hexaphenyltriphenylene, trihydroxytriptycene, and triaminotriptycene; and monomer 2 includes one of 2,3-dimethylindole, 5-methyl-2,3-indoledione, indoline, and indole-2,3-dione.
[0028] Preferably, the polymerization conditions are: polymerization temperature 40-50° C., and polymerization time 10-12 h.
[0029] Second active material layer:
[0030] The second active material layer includes the following components in mass percentage: 5-10% silicon-based material, 85-93% graphite material, 1-2% flexible binder, 0-2% high viscosity binder and 0.1-2% conductive agent.
[0031] The second active material layer is a mixed layer of silicon-based material and graphite in a low mass ratio, which contains a binder combination with good flexibility.
[0032] The silicon-based material is one or more selected from nano-silicon oxygen, nano-silicon carbon, silicon nanowires, and amorphous silicon alloys;
[0033] The graphite material is one or more selected from artificial graphite, natural graphite and mesophase carbon microspheres.
[0034] The high viscosity binder is one or more selected from polyacrylic acid, polyacrylonitrile, polytetrafluoroethylene, polyvinyl alcohol, and polybutyl acrylate;
[0035] The flexible binder is one or more selected from sodium carboxymethyl cellulose and styrene-butadiene rubber.
[0036] The conductive agent is one or more selected from conductive carbon black, carbon nanotubes, graphene, conductive graphite, and carbon fiber.
[0037] The silicon-based negative electrode sheet can be prepared by a layered coating method. First, the material of the second active material layer is made into a slurry and coated on the negative electrode collector to form the second active material layer. Then, the material of the first active material layer is made into a slurry and coated on the second active material layer to form the first active material layer.
[0038] Preferably, the surface density of the first active material layer is 20 to 50 g / m 2 The surface density of the second active material layer is 30 to 80 g / m 2 .
[0039] In a second aspect, the present invention provides a lithium-ion battery comprising the above-mentioned silicon-based negative electrode plate.
[0040] The lithium-ion battery includes a positive electrode plate, the above-mentioned silicon-based negative electrode plate, a diaphragm and an electrolyte; the positive electrode material of the positive electrode plate is one of lithium iron phosphate, lithium nickel cobalt manganese oxide, lithium manganese oxide and lithium cobalt oxide; the diaphragm is polyethylene, polypropylene and a coated diaphragm of the two; the electrolyte includes a mixture of carbonates, lithium salts and additives.
[0041] Beneficial effects:
[0042] (1) The silicon-based negative electrode provided by the present invention comprises two active material layers, wherein the first active material layer is a mixed layer of silicon-based negative electrode and graphite, and the silicon-based negative electrode has a high mass ratio and comprises a porous cross-linked polymer. The high mass ratio of the silicon-based negative electrode ensures a higher energy density, and the porous cross-linked polymer can effectively buffer the expansion of the electrode, reduce the internal stress of the electrode, and prevent the electrode from peeling and cracking; the second active material layer is a mixed layer of silicon-based negative electrode and graphite, and the silicon-based negative electrode material contains a lower mass ratio, which reduces the expansion and contraction of the electrode while ensuring a certain high energy density, and prevents the electrode from peeling off from the current collector; the design of the two active material layers ensures a high energy density, and at the same time, the formula design is optimized in combination with the bonding characteristics of the interface layer to prevent the generation of large internal stress during the charge and discharge process;
[0043] (2) The present invention applies an organic porous cross-linked polymer to the negative electrode plate. The polymer is loose and porous, and can undergo cross-linking polymerization during high temperature, making the negative electrode particles closer together, which can buffer the expansion of the silicon negative electrode during charging and discharging, and prevent the plate from peeling and cracking. At the same time, the polymer has certain adhesion and wettability, and can replace some commonly used sodium carboxymethyl cellulose and styrene-butadiene rubber to ensure the flexibility and adhesion of the plate;
[0044] (3) The design scheme of different active layer binders provided by the present invention further consolidates the performance of the negative electrode plate. The first active material layer uses a chain-shaped binder combination with strong adhesion to stabilize the expansion of the silicon-based negative electrode and prevent the silicon-based negative electrode from separating from the binder. The second active material layer uses a binder combination with better flexibility to buffer the expansion caused by the first active material layer, while increasing the flexibility of the plate and improving the processing performance of the plate.
[0045] The present invention has been described in detail above, but the above embodiments are only illustrative in nature and are not intended to limit the present invention. In addition, this article is not limited by any theory described in the above prior art or invention content or the following examples. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 This is a schematic diagram of the structure of the silicon-based negative electrode plate of the present invention;
[0047] Illustration: 1-negative electrode current collector; 2-second active material layer; 3-first active material layer. DETAILED DESCRIPTION
[0048] The present invention is further described below in conjunction with examples. It should be noted that the following examples are provided for illustrative purposes only and do not constitute a limitation on the scope of protection claimed for the present invention.
[0049] Unless otherwise specified, the raw materials, reagents, methods, etc. used in the examples are conventional raw materials, reagents, methods in the art.
[0050] Example 1
[0051] Preparation of negative electrode sheet: prepare the first active material layer with nano silicon carbon, artificial graphite, polyacrylic acid, styrene butadiene rubber, conductive carbon black and organic porous cross-linked polymer in a mass ratio of 40:55.5:2:0.5:1:1, the porous cross-linked polymer is prepared by dissolving 2,6,14-trihydroxytriptycene and 2,3-dimethylindole in chloroform solvent with the same molar ratio, and polymerizing in a reactor at 45°C for 10 hours; prepare the second active material layer with nano silicon oxide, artificial graphite, sodium carboxymethyl cellulose, styrene butadiene rubber and conductive carbon black in a mass ratio of 5:91:1.5:1.5:1; the above materials are uniformly dispersed in solvent deionized water to form slurry 1 and slurry 2, and then slurry 2 is applied on the current collector copper foil substrate, and then slurry 1 is applied on the surface of slurry 2, and the surface density of the first active material layer is 45g / m 2 The second active material layer density is 60g / m 2 , then transferred to an oven for drying, and rolled and cut to obtain the negative electrode sheets.
[0052] Example 2
[0053] Preparation of negative electrode sheet: prepare the first active material layer with nano-silicon oxide, artificial graphite, polyacrylonitrile, styrene-butadiene rubber, conductive carbon black and organic porous cross-linked polymer in a mass ratio of 50:46:2:1.5:1:0.5, the porous cross-linked polymer is prepared by dissolving 2,6,14-triaminotriphenylene and 5-methyl-2,3-indoledione in chloroform solvent with the same molar ratio, and polymerizing in a reactor at 45°C for 10 hours; prepare the second active material layer with nano-silicon oxide, artificial graphite, sodium carboxymethyl cellulose, polyacrylic acid and conductive carbon black in a mass ratio of 10:86:2:1:1; respectively disperse the above materials in solvent deionized water to form slurry 1 and slurry 2, then apply slurry 2 on the current collector copper foil substrate, and then apply slurry 1 on the surface of slurry 2, the surface density of the first active material layer is 40g / m 2 The second active material layer density is 55 g / m 2 , then transferred to an oven for drying, and rolled and cut to obtain the negative electrode sheets.
[0054] Example 3
[0055] Preparation of negative electrode sheet: prepare the first active material layer with nano silicon carbon, artificial graphite, polyacrylic acid, sodium carboxymethyl cellulose, conductive carbon black and organic porous cross-linked polymer in a mass ratio of 30:65.5:2:1:1:0.5, the porous cross-linked polymer is prepared by dissolving 2,6,14-trihydroxytriptycene and 2,3-dimethylindole in chloroform solvent with the same molar ratio, and polymerizing in a reactor at 45°C for 10 hours; prepare the second active material layer with nano silicon carbon, artificial graphite, sodium carboxymethyl cellulose, polyacrylic acid and conductive carbon black in a mass ratio of 5:91:2:0.5.:1; the above materials are uniformly dispersed in solvent deionized water to form slurry 1 and slurry 2, and then slurry 2 is applied on the current collector copper foil substrate, and then slurry 1 is applied on the surface of slurry 2, and the surface density of the first active material layer is 50g / m 2 The second active material layer density is 70 g / m 2 , then transferred to an oven for drying, and rolled and cut to obtain the negative electrode sheets.
[0056] Example 4
[0057] Preparation of negative electrode sheet: prepare the first active material layer with nano-silicon oxide, artificial graphite, polyacrylic acid, sodium carboxymethyl cellulose, conductive carbon black and organic porous cross-linked polymer in a mass ratio of 30:65.5:2.5:0.5:1:0.5, the porous cross-linked polymer is prepared by dissolving 2,6,14-triaminotriphenylene and 5-methyl-2,3-indoledione in chloroform solvent with the same molar ratio, and polymerizing in a reactor at 45°C for 10 hours; prepare the second active material layer with nano-silicon oxide, artificial graphite, carboxymethyl, styrene-butadiene rubber and conductive carbon black in a mass ratio of 5:92:1:1:1; respectively disperse the above materials in solvent deionized water to form slurry 1 and slurry 2, then apply slurry 2 on the current collector copper foil substrate, and then apply slurry 1 on the surface of slurry 2, the surface density of the first active material layer is 35g / m 2 The second active material layer density is 55g / m 2 , then transferred to an oven for drying, and rolled and cut to obtain the negative electrode sheets.
[0058] Example 5
[0059] Preparation of negative electrode sheet: prepare the first active material layer with nano silicon carbon, artificial graphite, polyacrylonitrile, styrene butadiene rubber, conductive carbon black and organic porous cross-linked polymer in a mass ratio of 30:65.5:2:1:1:0.5, the porous cross-linked polymer is prepared by dissolving 2,6,14-trihydroxytriptycene and 2,3-dimethylindole in chloroform solvent with the same molar ratio, and polymerizing in a reactor at 45°C for 10 hours; prepare the second active material layer with nano silicon oxide, artificial graphite, sodium carboxymethyl cellulose, styrene butadiene rubber and conductive carbon black in a mass ratio of 5:92:1:1:1; the above materials are uniformly dispersed in solvent deionized water to form slurry 1 and slurry 2, then slurry 2 is coated on the current collector copper foil substrate, and then slurry 1 is coated on the surface of slurry 2, and the surface density of the first active material layer is 35g / m 2 The second active material layer density is 55 g / m 2 , then transferred to an oven for drying, and rolled and cut to obtain the negative electrode sheets.
[0060] Comparative Example 1
[0061] Preparation of negative electrode sheet: prepare the first active material layer with nano silicon carbon, artificial graphite, polyacrylonitrile, styrene butadiene rubber and conductive carbon black in a mass ratio of 30:66:2:1:1; prepare the second active material layer with nano silicon oxide, artificial graphite, sodium carboxymethyl cellulose, styrene butadiene rubber and conductive carbon black in a mass ratio of 5:92:1:1:1; respectively disperse the above materials in solvent deionized water to form slurry 1 and slurry 2, then apply slurry 2 on the current collector copper foil substrate, and then apply slurry 1 on the surface of slurry 2. The layer density of the first active material layer is 35g / m 2 The second active material layer density is 55 g / m2 , then transferred to an oven for drying, and rolled and cut to obtain the negative electrode sheets.
[0062] Comparative Example 2
[0063] Preparation of negative electrode: Nano silicon carbon, artificial graphite, polyacrylonitrile, styrene-butadiene rubber, conductive carbon black, organic porous cross-linked polymer are prepared into active material layer in a mass ratio of 30:65.5:2:1:1:0.5. The porous cross-linked polymer is prepared by dissolving 2,6,14-triaminotriphenylene and 2,3-dimethylindole in chloroform solvent in the same molar ratio. The polymerization reaction is carried out in a reactor at 45°C for 10 hours. The above materials are uniformly dispersed in deionized water solvent to form a slurry, which is then coated on the current collector copper foil substrate with a surface density of 90 g / m 2 , then transferred to an oven for drying, and rolled and cut to obtain the negative electrode sheets.
[0064] Comparative Example 3
[0065] Preparation of negative electrode sheet: prepare the first active material layer with nano silicon carbon, artificial graphite, styrene butadiene rubber, sodium carboxymethyl cellulose, conductive carbon black and organic porous cross-linked polymer in a mass ratio of 30:65.5:2:1:1:0.5, the porous cross-linked polymer is prepared by dissolving 2,6,14-triaminotriphenylene and 2,3-dimethylindole in chloroform solvent with the same molar ratio, and polymerizing in a reactor at 45°C for 10 hours; prepare the second active material layer with nano silicon oxide, artificial graphite, sodium carboxymethyl cellulose, styrene butadiene rubber and conductive carbon black in a mass ratio of 5:92:1:1:1; the above materials are uniformly dispersed in solvent deionized water to form slurry 1 and slurry 2, then slurry 2 is coated on the current collector copper foil substrate, and then slurry 1 is coated on the surface of slurry 2, and the surface density of the first active material layer is 35g / m 2 The second active material layer density is 55 g / m 2 , then transferred to an oven for drying, and rolled and cut to obtain the negative electrode sheets.
[0066] Comparative Example 4
[0067] Preparation of negative electrode: Prepare active material layer with nano silicon carbon, artificial graphite, polyacrylonitrile, styrene butadiene rubber and conductive carbon black in a mass ratio of 30:66:2:1:1, evenly disperse the above materials in solvent deionized water to form slurry, and then apply the slurry on the current collector copper foil substrate. The active material layer density is 90g / m 2 , then transferred to an oven for drying, and rolled and cut to obtain the negative electrode sheets.
[0068] Test Case
[0069] The negative electrode sheets obtained in the examples and comparative examples were prepared into batteries:
[0070] Preparation of positive electrode sheets: The positive electrode material lithium nickel cobalt manganese oxide, conductive carbon black Super-P and binder polyvinylidene fluoride (PVDF) are mixed evenly in a mass ratio of 95:2:3, and then dispersed in N-methyl-2-pyrrolidone (NMP) to obtain positive electrode slurry, and then the slurry is evenly coated on both sides of the aluminum foil, and the positive electrode sheet is obtained after drying and rolling.
[0071] Preparation of the electrolyte: Ethylene carbonate and ethyl methyl carbonate are mixed in a mass ratio of 3:7 to obtain an organic solvent, and then lithium hexafluorophosphate with a mass dispersion of 13.5% is added to the solvent and mixed thoroughly.
[0072] The preparation steps of lithium-ion batteries are as follows: stack the positive electrode sheet, separator, and negative electrode sheet in order, ensure that the separator separates the positive electrode sheet and the negative electrode sheet, and the negative electrode sheet completely wraps the positive electrode sheet, and then put the stacked battery cell into an aluminum-plastic film packaging bag, and then inject the above-prepared electrolyte into the battery cell. After formation, sealing, aging, secondary sealing, capacity division and other processes, a battery with a capacity of 10000mAh is made.
[0073] The batteries prepared in the embodiments and comparative examples were subjected to storage and cycle performance tests. The storage test method was as follows: the divided batteries were charged to 4.3 V at a current of 1 C. After being fully charged, the batteries were placed in a high-temperature cabinet and stored at 55° C. for 28 days. The tested batteries were taken out and the battery voltage, capacity retention rate and capacity recovery rate were tested. The cycle test method was as follows: the divided batteries were charged and discharged at room temperature 25° C. and high temperature 45° C. at a current of 1 C. The cut-off voltage range was 2.5 to 4.3 V. The capacity retention rate after the cycle was calculated.
[0074] Table 1 Battery performance test results of the embodiments and comparative examples
[0075]
[0076] Analysis of results: In Examples 1 to 5, the negative electrode plate adopts a two-layer active material layer design. The first active material layer uses a combination of high-silicon-based materials, porous cross-linked polymers and high-viscosity binders, and the second layer adopts a low-silicon design, which ensures a high energy density design while reducing the expansion and contraction of the plate, avoiding peeling and cracking between the plate and the collector, and has the best capacity retention rate in high-temperature storage and long-term cycling. However, in Comparative Examples 1 to 4, which do not adopt the design of the present invention, the capacity decay is faster in storage and cycling. It can be seen that the silicon-based negative electrode plate design of the present invention has a significant improvement effect.
[0077] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents, without departing from the spirit and essence of the claims of the present invention; and these modifications or replacements are still within the scope defined by the claims of the present invention.
Claims
1. A silicon-based negative electrode plate, characterized in that: include: Anode current collector; a second active material layer disposed on at least one surface of the negative electrode current collector; a first active material layer disposed on a surface of the second active material layer; The first active material layer includes the following components in mass percentage: 30-50% silicon-based material, 42-66% graphite material, 2-3% high-viscosity binder, 0.5-2% flexible binder, 0.1-2% conductive agent and 0.5-2% porous cross-linked polymer, the organic porous cross-linked polymer is obtained by polymerization of monomer 1 and monomer 2, monomer 1 is selected from one of hexabromotriptycene, hexaaminotriptycene, hexaphenyltriphenylene, trihydroxytriptycene and triaminotriptycene; monomer 2 is selected from one of 2,3-dimethylindole, 5-methyl-2,3-indoledione, indoline and indole-2,3-dione; The second active material layer includes the following components in mass percentage: 5-10% silicon-based material, 85-93% graphite material, 1-2% flexible binder, 0-2% high viscosity binder and 0.1-2% conductive agent; The high viscosity binder is one or more selected from polyacrylic acid, polyacrylonitrile, polytetrafluoroethylene, polyvinyl alcohol, and polybutyl acrylate; The flexible binder is one or more selected from sodium carboxymethyl cellulose and styrene-butadiene rubber.
2. The silicon-based negative electrode plate according to claim 1, characterized in that: The silicon-based material in the first active material layer is one or more selected from nano-silicon oxygen, nano-silicon carbon, silicon nanowires, and amorphous silicon alloys.
3. The silicon-based negative electrode plate according to claim 1, characterized in that: The graphite material in the first active material layer is one or more selected from artificial graphite, natural graphite and mesophase carbon microbeads.
4. The silicon-based negative electrode plate according to claim 1, characterized in that: The conductive agent in the first active material layer is one or more selected from conductive carbon black, carbon nanotubes, graphene, conductive graphite, and carbon fiber.
5. The silicon-based negative electrode plate according to claim 1, characterized in that: The method for preparing the organic porous cross-linked polymer in the first active material layer comprises: The monomer 1 and the monomer 2 are dissolved in chloroform solvent and stirred at a uniform speed, and the polymerization reaction is carried out in a reactor at 40-50° C. for 10-12 hours. The reaction polymer is filtered and dried to obtain an organic porous cross-linked polymer.
6. The silicon-based negative electrode plate according to claim 1, characterized in that: The silicon-based material in the second active material layer is one or more selected from nano-silicon oxygen, nano-silicon carbon, silicon nanowires, and amorphous silicon alloys.
7. The silicon-based negative electrode plate according to claim 1, characterized in that: The graphite material in the second active material layer is one or more selected from artificial graphite, natural graphite and mesophase carbon microbeads.
8. The silicon-based negative electrode plate according to claim 1, characterized in that: The conductive agent in the second active material layer is one or more selected from conductive carbon black, carbon nanotubes, graphene, conductive graphite, and carbon fiber.
9. The silicon-based negative electrode plate according to claim 1, characterized in that: The surface density of the first active material layer is 20 to 50 g / m 2 The surface density of the second active material layer is 30 to 80 g / m 2 .
10. A lithium ion battery, characterized in that: Comprising the silicon-based negative electrode plate as described in any one of claims 1-9.
Citation Information
Patent Citations
Silicon-containing negative plate and high-energy density battery
CN113066962A
Non-aqueous electrolyte secondary cell and device using the same
CN1349672A
Electrode active mateiral for secondary battery, and the secondary battery comprising the same
KR1020180118077A
Image decoding apparatus and image encoding apparatus for adaptive quantization and inverse-quantization, and methods thereby
KR1020240025428A
Cited By
Negative plate, battery and electric equipment
CN122474574A
A negative electrode sheet, a method for manufacturing the same, and use thereof
CN122696634A